Barriers of implementing balanced scorecard in Jordan: a case study of Jordanian banks - Syamsul Azri, Abdul Rahman; Abd Al-Rahman, Jaradat (2020)
This study aimed to find the existing barriers facing Balanced Scorecard implementation as a performance measurement and management tool in the Jordanian banks. Qualitative research using open-ended questions. semi-structured interviews were conducted with nine Jordanian commercial bank managers. The data was analyzed using cross-case analysis. The study revealed the barriers and hinders that affect the balanced scorecard implementation as a management strategy, such as lack of knowledge, lack of (IT) support, and not involving the whole bank's employees, employees resistant to apply such strategy. The Findings also demonstrate that the Jordanian banks evaluated the performance of the bank including several aspects financial, customer, internal system, education and development similar to BSC dimensions.